Evan Jones (ed.), Intimate Voices: the Twentieth-Century String Quartet (2009) - Russ, Michael (Journal of the Society for Musicology in Ireland, 2011)
Review of Evan Jones (ed.), Intimate Voices: the Twentieth-Century String Quartet (Rochester: University of Rochester Press, 2009). Volume I: Debussy to Villa-Lobos, ISBN 978-1-58046-229-7; Volume 2: Shostakovich to the Avant-Garde, ISBN 978-1-58046-322-5.